2020
DOI: 10.1038/s41598-020-75866-0
|View full text |Cite
|
Sign up to set email alerts
|

Twist2 is NFkB-responsive when p120-catenin is inactivated and EGFR is overexpressed in esophageal keratinocytes

Abstract: Esophageal squamous cell carcinoma (ESCC) is among the most aggressive and fatal cancer types. ESCC classically progresses rapidly and frequently causes mortality in four out of five patients within two years of diagnosis. Yet, little is known about the mechanisms that make ESCC so aggressive. In a previous study we demonstrated that p120-catenin (p120ctn) and EGFR, two genes associated with poor prognosis in ESCC, work together to cause invasion. Specifically, inactivation of p120ctn combined with overexpress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Through the combined analysis of metabolomics and network pharmacology, it can be seen that QB mainly interfere with the G alpha (q) signaling events, GPCR downstream signaling, signal transduction, signaling by GPCR, spinal cord injury, GnRH signaling pathway, relationship between inflammation COX-2 and EGFR, and other interventions in the disease process, mainly the intervention of G-protein–coupled receptors, and EGFR. Through the analysis of the combined path of the two, G-protein–coupled receptors can directly promote the activation of the PI3K pathway ( Li et al, 2021 ), while EGFR directly promotes the expression of Twist2 ( Lehman et al, 2020 ). Both the STAT3 and PI3K pathways act as the direct upstream of the NF-κB pathway, directly or through Twist2, promoting the activation of the NF-κB pathway ( Figure 10 ).…”
Section: Resultsmentioning
confidence: 99%
“…Through the combined analysis of metabolomics and network pharmacology, it can be seen that QB mainly interfere with the G alpha (q) signaling events, GPCR downstream signaling, signal transduction, signaling by GPCR, spinal cord injury, GnRH signaling pathway, relationship between inflammation COX-2 and EGFR, and other interventions in the disease process, mainly the intervention of G-protein–coupled receptors, and EGFR. Through the analysis of the combined path of the two, G-protein–coupled receptors can directly promote the activation of the PI3K pathway ( Li et al, 2021 ), while EGFR directly promotes the expression of Twist2 ( Lehman et al, 2020 ). Both the STAT3 and PI3K pathways act as the direct upstream of the NF-κB pathway, directly or through Twist2, promoting the activation of the NF-κB pathway ( Figure 10 ).…”
Section: Resultsmentioning
confidence: 99%
“…To date, the interconnection between H 2 O 2 signaling and EMT in cancer is well established (Milton and Konrad, 2022), and the role of H 2 O 2 producers NADPH oxidase 4 (NOX4), dual oxidase 1 (DUOX1) and DUOX2 in cell motility and metastasis in cancer biology has been reviewed (Meitzler et al, 2019). Regarding NF-κB, it was demonstrated that inhibiting its activity resulted in an almost complete loss of expression of the Twist2 gene (Lehman et al, 2020). The effects of activating the JAK/STAT3 signaling pathway on EMT and the generation of CSCs have also been documented (Jin 2020).…”
Section: Major Findings Relevant To Other Signaling Pathwaysmentioning
confidence: 99%
“…In addition to the morphological changes, EMTcells possess stem cell properties. This phenomenon enables EMT and GSCs regulation by similar pathways, including the WNT, STAT3 and NF-κB and Hedgehog pathways (58,59). The PI3K/AKT/mTOR signal pathway is a classical pathway regulating cell growth and differentiation.…”
Section: Cscs and Emtmentioning
confidence: 99%